Growth-Financial Intermediation Nexus in China - Aziz, Jahangir; Duenwald, Christoph (Washington, D.C. : International Monetary Fund, 2002)
This paper studies the relationship between economic growth and financial development in China during the post-1978 reform period. Recent studies, based on cross-country data, have found a positive association between these two variables. We find that while a positive correlation between growth and financial intermediation exists in China, the association is more apparent than real. The nonstate sector, which contributed most to China's remarkable growth during this period, did not use the domestic financial system in any substantial way for financing. The same appears to be true for the faster-growing provinces. Compared to foreign investment, domestic private credit played a relatively small, although statistically significant, role in financing the nonstate sector and fast-growing provinces.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet